2020
DOI: 10.1007/s00403-020-02091-0
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of skin lesions during the evolution of COVID-19: a case report

Abstract: The disease caused by the new coronavirus (COVID-19) has many systemic manifestations affecting the upper airways, lungs, gastrointestinal tract and inducing hematological repercussions. With the evolution of the pandemic, skin lesions were observed. However, there is little information about the evolution of the lesions at this moment. The authors report a case of a patient who had more than one exposure to the coronavirus during the evolution of the disease and manifested different types of edematous lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 13 publications
(11 reference statements)
0
34
0
5
Order By: Relevance
“…Similarly, an extensive review of 997 patients from 9 different countries analyzed by Jia et al found that approximately 22% of patients had urticarial eruptions [4••]. Urticaria with or without angioedema in the setting of confirmed or highly suspected COVID-19 infection has been observed in several reports and case series [2,5,[39][40][41][42][43][44][45][46][47]. Similar to other viral infections, urticarial rash may precede or occur simultaneously with COVID-19 systemic manifestations (i.e., fever, cough) and last for several days [5,39,43,44,47,48].…”
Section: Urticaria and Angioedemamentioning
confidence: 99%
“…Similarly, an extensive review of 997 patients from 9 different countries analyzed by Jia et al found that approximately 22% of patients had urticarial eruptions [4••]. Urticaria with or without angioedema in the setting of confirmed or highly suspected COVID-19 infection has been observed in several reports and case series [2,5,[39][40][41][42][43][44][45][46][47]. Similar to other viral infections, urticarial rash may precede or occur simultaneously with COVID-19 systemic manifestations (i.e., fever, cough) and last for several days [5,39,43,44,47,48].…”
Section: Urticaria and Angioedemamentioning
confidence: 99%
“…After eliminating the overlaps between the two search engines, we were left with 23 works investigating the relationships between SARS-CoV-2 infection and urticaria. Of these, 18 reported cases of urticaria in patients with SARS-CoV-2 infection [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Unfortunately, not all studies reported the characteristics of the patients studied (gender, age, timing, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…The other works selected reported up to two cases of urticaria. Generally, the lesions vanished rapidly following the application of local corticosteroids and the use of oral antihistamines [22] or within 10 days after the onset [23].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, other manifestations similar to cutaneous autoimmune vasculitis, including symmetric perimalleolar urticaria and vasculitic purpura have been observed in COVID-19 patients [16]. Also, prodromal erythematous-edematous plaques in elbow and knee joints that latter evolve to urticarial lesions have been reported in a patient from Brazil [22]. Meanwhile, no evidence of mucosal involvement has been reported so far, although some studies have demonstrated that the incidence of conjunctivitis is an important clinical finding in severely ill patients [67].…”
Section: Other Manifestationsmentioning
confidence: 99%
“…The spectrum of mucocutaneous manifestations of SARS-CoV-2 infection Other cutaneous manifestations reported in COVID-19 patients include maculopapular lesions resembling pityriasis rosea, erythema elevatum diutinum, erythema multiforme, Grover disease, cutaneous vasculitis, and elbow/knee joint erythematous-edematous plaques[16,22,25,32,49,83,84] …”
mentioning
confidence: 99%